Raphe-Type Bicuspid Aortic Valve as a Risk Factor for Transcatheter Aortic Valve Replacement Failure: Improving Outcomes Using the LIRA Method and the Medtronic FX Prosthesis - Francesca Napoli; Barbara Bellini; Vittorio Romano; Greca Zanda; Ciro Vella; Filippo Russo; Luca Angelo Ferri; Marco Bruno Ancona; Paolo Bonfanti; Eustachio Agricola; Antonio Esposito; Matteo Montorfano (Journal of Cardiovascular Development and Disease, 2024)
Transcatheter aortic valve replacement (TAVR) in patients with severe aortic stenosis and raphe-type bicuspid aortic valve (BAV) is still associated with poor outcomes in terms of increased risk of paravalvular regurgitation, stroke, and permanent pacemaker implantation. There is no definitive consensus on the optimal sizing method for prosthesis selection in this setting. The LIRA method is a supra-annular tailored sizing method specifically designed for bicuspid anatomy that might increase accuracy of prosthesis choice in BAV patients and improve TAVR outcomes. This is the first report of the combination of the novel LIRA method for prosthesis sizing together with the adoption of the technological improvements introduced by the Evolut FX prosthesis as a useful tool for improving outcomes in this high risk subgroup of patients.